Description of the degree of nonuniqueness in inverse source problems - Ramm, Alexander G. (My University, 1998)
For time-independent and time-dependent inverse source problems the degree of nonuniqueness of solutions is characterized.
Keywords: Nonuniqueness; Inverse source problems